Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field*. (27th September 2020) - Liu, Liyuan; Xing, Fangfang; Li, Yabing; Han, Yingchun; Wang, Zhanbiao; Zhi, Xiaoyu; Wang, Guoping; Feng, Lu; Yang, Beifang; Lei, Yaping; Fan, Zhengyi; Du, Wenli
Abstract: The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely. Résumé: La quantification précise du mouvement de l'eau dans les différentes couches de sol des champs est importante pour l'irrigation et la fertilisation à débit variable. À cette fin, une expérience in‐situ basée sur une approche géostatistique a été menée dans le sud d'Anyang, Henan, Chine, pour examiner le mouvement de l'eau du sol dans un champ de coton avec irrigation goutte à goutte en mesurant les données de teneur en eau du sol (SWC) sur une base régulière de 100 × 80 cm la grille. Le résultat a montré que la variation temporelle et spatiale de l'humidité du sol diminuait avec l'augmentation de la profondeur du sol à différents points, et une hétérogénéité spatiale apparente a été observée dans différentes conditions du sol grâce à une analyse par semi‐variogramme. La variation de l'humidité du sol à différents profils de sol a été affectée par les plants de coton et les lignes de goutte‐à‐goutte pendant la période de non‐irrigation et la période d'irrigation respectivement. Le niveau de changement à 20 cm était de plus de 70 cm dans le sens horizontal aux deux périodes, cependant le degré de changement à 40 cm dans la période d'irrigation était de plus de 70 cm dans le sens vertical, tandis que les résultats contraires ont été montrés à la période de non‐irrigation. De plus, les résultats ont indiqué que la règle trapézoïdale pouvait être appliquée pour quantifier avec précision le volume de mouvement de l'eau.